Prevalence of resurgence during thinning of multiple schedules of reinforcement following functional communication training. Issue 2 (25th October 2020) - Muething, Colin; Pavlov, Alexis; Call, Nathan; Ringdahl, Joel; Gillespie, Scott
Abstract : The current study examined resurgence of problem behavior during thinning of multiple schedules of reinforcement following functional communication training replicating previous research (Briggs et al., 2018). Data were analyzed at each thinning step from subjects enrolled in an intensive day treatment program over a 5‐year period. Results indicated that of the 239 thinning steps analyzed, resurgence was observed in 97 of those steps (40.6%), similar to results of Briggs et al. (2018). The data were also analyzed to estimate the magnitude of resurgence when it was observed. In the first session after the thinning step, the rate of problem behavior observed was 7 times higher than the average of the 5 sessions pre‐thinning step.